Bacterial cell membranes and their role in daptomycin resistance: A review - Nguyen, April H.; Hood, Kara S.; Mileykovskaya, Eugenia; Miller, William R.; Tran, Truc T. (Frontiers in Molecular Biosciences, 2022)
Lipids play a major role in bacterial cells. Foremost, lipids are the primary constituents of the cell membrane bilayer, providing structure and separating the cell from the surrounding environment. This makes the lipid bilayer a prime target for antimicrobial peptides and membrane-acting antibiotics such as daptomycin. In response, bacteria have evolved mechanisms by which the membrane can be adapted to resist attack by these antimicrobial compounds. In this review, we focus on the membrane phospholipid changes associated with daptomycin resistance in enterococci, Staphylococcus aureus, and the Viridans group streptococci.